2014
DOI: 10.5935/1678-9741.20140013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of periodontal therapy on C-reactive protein and HDL in serum of subjects with periodontitis

Abstract: Rev Bras Cir Cardiovasc | Braz J Cardiovasc SurgRev Bras Cir Cardiovasc 2014;29(1):69-77 Leite ACE, et al. -Effects of periodontal therapy on C-reactive protein and HDL in serum of subjects with periodontitis RBCCV 44205-152344205- DOI: 10.5935/1678 Effects of periodontal therapy on C-reactive protein and HDL in serum of subjects with periodontitis Efeitos da terapia periodontal sobre proteína C-reativa e HDL no soro de indivíduos com periodontite ORIGINAL ARTICLE Abstract Objective: To investigate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 20 publications
2
11
0
4
Order By: Relevance
“…Additionally, rigorous therapeutic protocols and periodontal maintenance contributed to the restoration of phagocytic function in peripheral blood neutrophils (Carneiro et al, 2012) and a reduction in hs-CRP levels in patients with severe periodontitis (Leite et al, 2014). These findings also support the conclusions of D' Aiuto et al (2004b;2004c) and Kamil et al (2011) when reporting a greater reduction in the levels of systemic inflammatory markers among those with better clinical responses to periodontal therapy.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Additionally, rigorous therapeutic protocols and periodontal maintenance contributed to the restoration of phagocytic function in peripheral blood neutrophils (Carneiro et al, 2012) and a reduction in hs-CRP levels in patients with severe periodontitis (Leite et al, 2014). These findings also support the conclusions of D' Aiuto et al (2004b;2004c) and Kamil et al (2011) when reporting a greater reduction in the levels of systemic inflammatory markers among those with better clinical responses to periodontal therapy.…”
Section: Discussionsupporting
confidence: 79%
“…In a previous study by our group, we found levels of high-sensitivity C-reactive protein (hs-CRP) >0.3 mg/dL in individuals with severe periodontitis compared to controls (60.87 versus 23.08, respectively; p = 0.0216) (Leite et al, 2014) and periodontal therapy was associated with a decrease in hs-CRP levels circulating in serum and an increase in High Density Lipoprotein (HDL).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Moderate to severe periodontitis has been linked to increased serum levels of either CRP (Christodoulides et al 2007, Giannopoulou et al 2012, Nakajima et al 2010, Zhang et al 2013, Bokhari et al 2014, Caúla et al 2014, Kumari et al 2014, Arregoces et al 2014, Leite et al 2014, Kalburgi et al 2014, Sharma et al 2014), or ProCT (Bassim et al 2008, Giannopoulou et al 2012), which are two acute-phase inflammatory markers. Salivary CRP (Pederson et al 1995, Christodoulides et al 2007, Ouellet-Morin et al 2011, Foley et al 2012) and ProCT (Bassim et al 2008) levels also have been shown to be higher in patients with moderate to severe periodontitis than in patients with an essentially healthy periodontium.…”
mentioning
confidence: 99%